Catalytic asymmetric synthesis of tetrahydrocarbazoles - Tan, Fen; Cheng, Hong-Gang (Chemical communications (Cambridge, England), 2019)
Chiral tetrahydrocarbazoles (THCs) are prevalent in numerous natural indole alkaloids as well as synthetic pharmaceuticals, and exhibit a broad spectrum of bioactivities. As such, the development of efficient synthetic methodologies for the synthesis of chiral THCs is of substantial interest. The advent of asymmetric catalysis provides a powerful platform to assemble chiral THC motifs and great efforts have been devoted to this field over the past decades. In this feature article, we summarise recent advances in catalytic asymmetric synthesis of THCs, with particular emphases on reaction types and reaction mechanism. This feature article summarises recent advances in catalytic asymmetric synthesis of THCs, with emphases on reaction type and reaction mechanism.